Understanding the spectrum of sinus venosus interatrial communications. (10th May 2016) - Tretter, Justin T.; Chikkabyrappa, Sathish; Spicer, Diane E.; Backer, Carl L.; Mosca, Ralph S.; Anderson, Robert H.; Bhatla, Puneet
Abstract: Background: It is still thought by some that a common wall is to be found in the normal heart between the attachments of the caval and pulmonary veins, with absence of this wall underscoring the presence of sinus venosus defects. Recent findings using episcopic microscopy in developing mice have shown the deficiencies of this notion. Understanding that the superior rim of the oval fossa is a fold, rather than a true septum, which can be distorted in the presence of partially anomalous pulmonary venous drainage, has provided an alternative explanation for the morphogenesis of sinus venosus defects. Methods: We reviewed our experience with patients suspected of having a sinus venosus defect from August, 2011, through October, 2015, analysing the findings in light of the current hypotheses used to explain the development of the defects, along with correlations made by inspection of autopsy specimens. Results: We evaluated findings from 16 patients, with a mean age of 7.7 years, ranging from 2.7 to 15 years. Of the group, 13 were ultimately diagnosed with a superior sinus venosus defect, two with an inferior defect, and one with isolated anomalous pulmonary venous connection in the absence of an interatrial communication. Initially, two patients were thought to have oval fossa defects, one from each subtype, but were correctly diagnosed following cardiac magnetic resonance interrogation. Anomalous pulmonary venous connections were present in all cases. Conclusion: Appreciation of the changes occurring during normal cardiac development helps in understanding the anatomical substrate underscoring the spectrum of sinus venosus defects. The lesions are veno-venous connections due to partially anomalous pulmonary venous connections, producing interatrial communications outside the confines of the interatrial septum.